Comparative analysis on industry operating performance efficiency - Abdullah, Fader; Ismail, Ahmad; Ku-Mahamud, Ku Ruhana; Mat Kasim, Maznah (2012)
This paper presents a comparative study on the operating efficiency of companies from various industries.A total of 189 top performance companies from seven industries listed in Kuala Lumpur Composite Index were used in the efficiency strength and return to scale analyses.The input oriented Data Envelopment Analysis models were employed in the analyses.Data were obtained from the annual financial statement for the year 2012.On average, the operational efficiency level of the companies were only three quarters and over half of the total number of companies were operating below average efficiency level.Only a small number of companies will remain efficient in their operations while the rest will have difficulty in making themselves efficient in short term. About half of the total number of companies was operating with minimum cost to achieve maximum output.